Optimization Of Flame Stabilization Limits In Meso-Scale Tube Combustors With Wire Mesh - Abdul Munir, Fudhail; Seo, Takehiko; Mikami, Masato (IJENS Publisher, 2017)
In the last two decades, with the continued depletion of energy resources and the need for better power sources for small scale devices, researchers have become increasingly interested in meso and micro-scale combustion. Flame stability of a meso-scale combustor depends on a few important factors such as combustor wall thickness, wall thermal conductivity and inner diameter. In order to enhance the combustor performance such as the operational limits, it is vital to fundamentally understand these determinant factors. In this research, simulations and experiments were performed to investigate the factors affecting the flame stabilization in meso- scale tube combustors with stainless steel wire mesh. The inner diameter of the meso-scale cylindrical tube combustors is fixed to 3.5 mm while the wall thickness is maintained at 0.7 mm. The wire mesh is located between the unburned and burned gas region of the combustor. The numerical simulations were performed using a three-dimensional (3-D) numerical model, from which the results in terms of gas and wire mesh temperature contours, blowout limits, combustor outer wall temperature distribution and combustion efficiency were established. In the experiments, the equivalence ratio and mixture flow velocity were varied and the effects in terms of flame stabilization limits were recorded. The main objective of utilizing a 3-D numerical model is to successfully demonstrate the role of thermal path from the tube combustor wall to the wire mesh in enhancing the flame stabilization near the blowout limits. The numerical results show that the direction of the thermal path plays a significant role in improving the blowout limits. It is also demonstrated that more heat can be recirculated to the unburned gas region with the use material with higher wall thermal conductivity in burned gas region. As a result, the flame stabilization limits can be enhanced.